Study of relationships between HLA-G gene polymorphism, intrauterine infection and recurrent miscarriage in women - L. A. Gordeeva; E. N. Voronina; E. G. Polenok; S. A. Mun; S. L. Nersesyan; R. V. Olennikova; M. L. Filipenko; A. N. Glushkov (Медицинская иммунология, 2021)
The relationship between the HLA-G gene polymorphism (rs41551813, rs12722477, rs41557518), intrauterine infection and recurrent miscarriage (RM) in women were studied. The case group consisted of 180 patients with RM, defined as two or more consecutive miscarriages (min = 2; max = 8) at up to 20 weeks of gestation, and with clinically confirmed pregnancies and non-viable fetuses. At the time of examination. the women were enrolled from the Genetic Counseling Center at the Kemerovo Regional Clinical Hospital, Kemerovo, Russia, and were not pregnant. Each patient underwent a gynecological examination. We excluded women with a history of medical abortion, birth, and ectopic pregnancies. In addition, we excluded women with endocrine (e.g. diabetes) disorders. To exclude other known causes of spontaneous abortion, the following tests were performed: ultrasound examination of pelvic organs, and karyotyping in women and men. The women’s mean age in the RM group, was 29.6±4.8 (SD) years. The control group comprised 408 fertile women. These women didn’t have a history of spontaneous abortion, or a family history of congenital malformations. They have born, at least, 1-2 healthy children. Women’s mean age at birth of last child was 26.8±5.2 (SD) years. Influence of the intrauterine infection was analyzed on the basis of laboratory tests. Diagnostics of bacterial vaginosis and vulvo-vaginal candidiasis by microscopic examination was conducted. Viral agent infections (herpes simplex virus type 2, cytomegalovirus, human papilloma virus type 16/18), Chlamydia trachomatis, Mycoplasma hominis, Ureaplasma urealyticum, Gardnerella vaginalis and Trichomonas vaginalis were detected by enzyme-linked immunoassay and polymerase chain reaction (PCR). The data were obtained from the medical cards of the surveyed women. All the women gave a written informed consent before participating in the study. Typing of polymorphisms of Thr31Ser (rs41551813, HLA-G*01:03) in exon 2, Leu110Ile (rs12722477, HLA-G*01:04) and 1597 delС (rs41557518, HLA-G*01:05N) in exon 3 HLA-G genes were performed by realtime PCR followed by melting analysis. The study showed that the intrauterine infection was not a risk factor for RM (p = 0.30) in the examined women. It was found that the 110 Ile allele (HLA-G *01:04) was a risk factor for RM both in women with intrauterine infection [ORa = 4.50 (2.41-8.38), p = 2.09e-06], and in women without infection [ORa = 2.46 (1.44-4.21), p = 0.0009]. The cooperative influence of genetic and infections factors with the risk of RM in women was revealed [ORa+f = 3.50 (2.01-6.09), p = 8.78e-06]. Our results will be useful in understanding the molecular mechanisms of immune disorders in fetomaternal interface, and for choosing the strategy of management and treatment in women with RM.